Internal marketing, job satisfaction and employee engagement in commercial enterprises - Del Rosario Ángel, Lizeth Anabel; Feijoo Jaramillo, Irene María; Sarmiento Chugcho, Carlos Bolívar; Ramón Ramón, Dolores Isabel (Revista Universidad de Guayaquil, 2024)
The main objective of this research is to analyse the influence between internal marketing on job satisfaction and employee commitment. The results revealed a (x2=172.55, G=-0.98, T=8.20, p˂.001), significant relationship which supports H1. Regarding H2, the results present a significant relationship (x2=198.06, G=0.99, T=8.31, p˂.001) being enough to support H2. The analyses showed that the Gamma values are very close to 1, so it is concluded that employees highly value the dedication and importance that their company gives to set up a work environment that contributes to their satisfaction labor.